Comparative Sexual Outcomes of Laparoscopic Davydov and SIS Graft for Neovagina in MRKH Patients: Meta-Analysis - Wael Oemar; Tyas Priyatini (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction: Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a rare congenital anomaly of the female reproductive system, characterized by the absence of the uterus and upper vagina. Neovaginal reconstruction is the primary treatment to enable normal sexual function. Two commonly used techniques are the laparoscopic Davydov procedure and the use of Small Intestine Submucosa (SIS) grafts. Methods: A systematic review and meta-analysis were conducted on studies comparing these two surgical techniques in MRKH patients. Literature searches were performed through multiple international databases. Inclusion criteria involved both observational and experimental studies reporting anatomical and sexual function outcomes postoperatively. Statistical analysis was performed to compare the outcomes of both techniques. Results: The review found that both techniques are effective in achieving satisfactory anatomical and functional neovagina creation. However, differences were observed in parameters such as duration of molding use, vaginal length, and FSFI domain scores. The laparoscopic Davydov procedure showed advantages in anatomical outcomes and shorter molding duration, while SIS grafts demonstrated better scores in some subjective aspects of sexual function. Conclusion: Both the laparoscopic Davydov procedure and SIS grafts are effective in neovagina creation for MRKH patients. The Davydov technique offers superior anatomical results and reduced postoperative dilation time, whereas SIS grafts may provide improved sexual desire, arousal, and satisfaction. Further studies with larger and more diverse populations are needed to validate these findings.